Ion milling-induced micrometer-sized heterogeneities and partial crystallization in a TiZrCuFeBe bulk metallic glass. (June 2016) - Zhang, L.; Pauly, S.; Zhu, Z.W.; Gemming, T.; Fu, H.M.; Eckert, J.; Zhang, H.F.
Abstract: The Ti36.2 Zr30.3 Cu8.3 Fe4 Be21.2 (at.%) bulk metallic glass (BMG) exhibits a regular micrometer-sized pattern in the transmission electron microscope (TEM) after ion milling. Quantitative energy-dispersive X-ray spectroscopy (EDX) results show that the compositions in the bright and dark regions are distinctly different, and the compositions gradually change with the contrast of the pattern. In the intermediate regions (with grey contrast) preferential crystallization is observed and this confirms that microscale heterogeneities exist in the ion-milled TEM specimens. On the contrary, the specimens prepared by focused ion beam and by electrolytic thinning show featureless microstructures in the TEM. Moreover, EDX results and the secondary ion mass spectroscopy show that the constituent elements are homogeneously distributed. An ion milling-induced compositional fluctuation mechanism is proposed, and the partial devitrification can be explained based on this mechanism. The present findings may lead to a deeper understanding of the occurrence of micrometer-sized heterogeneities in BMGs induced by ion milling. Graphical abstract: Highlights: TEM specimens prepared by ion milling show regular micrometer-sized patterns. Compositions are changing within these patterns. Certain regions (compositions) show preferential partial crystallization. TEM specimens prepared by electrolytic thinning show a uniform microstructure. A mechanism for ion milling-induced preferential crystallization is proposed.